History of International Refugee Immigration Law in Indonesia - Cahyo Arsetyo, Yulio Iqbal (JURNAL PENELITIAN SERAMBI HUKUM, 2024)
This article provides an overview of Indonesia's historical involvement with international refugee immigration law, focusing on its relationship with the UNHCR and its handling of refugee crises. Despite not ratifying the 1951 Refugee Convention, Indonesia has internal regulations for refugees and a history of providing protection to political asylum seekers. The article highlights the need for new laws to regulate immigration and refugee flow, particularly in light of the Rohingya crisis, and emphasizes the necessity for stronger and more specific laws to address rights of refugees in Indonesia.